2019
DOI: 10.3390/medicina55070316
|View full text |Cite
|
Sign up to set email alerts
|

An Immunohistochemical Study of Gastric Mucosa and Critical Review Indicate That the Subepithelial Telocytes Are Prelymphatic Endothelial Cells

Abstract: There are only a few studies regarding gut subepithelial telocytes (TCs). The telopodes, namely peculiar TCs’ prolongations described on two-dimensional cuts, are not enough to differentiate this specific cell type. Subepithelial TCs were associated with the intestinal stem niche but a proper differential diagnosis with lymphatic endothelial cells (LECs) was not performed. In this study, we will critically review studies suggesting that distinctive TCs could be positioned within the lamina propria. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…But, in addition to hematopoietic cells, there is evidence that CD34 is present on the surface of a series of adult progenitor cells in several organs (Sidney, Branch, Dunphy, Dua, & Hopkinson, 2014). There are CD34‐positive cells of progenitor potential related to blood vessels, such as perivascular mesenchymal stem cells (Özen et al, 2012), in addition to lymphatic endothelial progenitors (Rossi et al, 2010; Tan et al, 2014) and, finally, CD34‐positive stromal cells, which comprise so‐called telocytes (Popescu & Faussone‐Pellegrini, 2010). A recent study pointed out that part of what we call telocytes would be actually pre‐lymphatic endothelial cells, which would be CD34‐ and CD31‐positive cells (Toader et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, in addition to hematopoietic cells, there is evidence that CD34 is present on the surface of a series of adult progenitor cells in several organs (Sidney, Branch, Dunphy, Dua, & Hopkinson, 2014). There are CD34‐positive cells of progenitor potential related to blood vessels, such as perivascular mesenchymal stem cells (Özen et al, 2012), in addition to lymphatic endothelial progenitors (Rossi et al, 2010; Tan et al, 2014) and, finally, CD34‐positive stromal cells, which comprise so‐called telocytes (Popescu & Faussone‐Pellegrini, 2010). A recent study pointed out that part of what we call telocytes would be actually pre‐lymphatic endothelial cells, which would be CD34‐ and CD31‐positive cells (Toader et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown great complexity in stromal cells, evidenced by the heterogeneity of fibroblasts in terms of morphological and possibly functional markers, especially on the skin (Driskell & Watt, 2015; Lemons et al, 2010; Lynch & Watt, 2018). As well as the presence of several types of CD34‐positive cells, such as vascular endothelial progenitors (Özen, Boix, & Paul, 2012), lymphatic endothelial progenitors (Rossi et al, 2010; Tan et al, 2014), and fibroblast‐like cells, the so‐called telocytes, were found in various organs. Telocytes were initially described by Popescu and Faussone‐Pellegrini (2010); these cells have a characteristic morphology, with thin cytoplasmic extensions, the telopodes that have dilations called podoms, which in turn have organelles such as mitochondria and endoplasmic reticules, something not found in fibroblasts.…”
Section: Introductionmentioning
confidence: 99%
“…26 Various studies regarding TCs have attempted to identify specific functional characteristics of these cells, but they often have not used unitary scientific methodology, as recently reported. 9,11,14,[27][28][29][30][31] However, despite the controversies regarding TCs, [9][10][11]32 they should be included in both the nomenclature and textbooks of histology. 33 Nevertheless, care should be taken on two-dimensional slices, as tangentially cut endothelial cells, or lymphatic capillaries, could generate false evidence of TCs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this panel of markers is equally suited to detect lymphatics, and also to distinguish them from TCs 7 . Initial TCs studies failed to use a specific lymphatic marker to discriminate them from LECs, as recently discussed 8‐11 . Caution should be taken in immunohistochemistry because TCs and endothelial tip cells (guides of angiogenic sprouts) may share a comparable morphology 12‐14 …”
Section: Introductionmentioning
confidence: 99%
“…Thus, there are groups that maintain the terminology of CD34‐positive fibroblasts, but these groups do not generally work with ultrastructural data. There is also a criticism that some of the telocytes detected in the tissue would be prelymphatic endothelial cells, which are also CD34‐positive (Toader et al, 2019). However, a study has revealed that telocytes also exist around lymphatic vessels and that prelymphatic endothelial cells are generally CD34‐negative (Rosa, Marini, Sgambati, Ibba‐Manneschi, & Manetti, 2020).…”
Section: Introductionmentioning
confidence: 99%